The synthesis and spectral characterization of N,N-Bis(2-{[(2-methyl-2-phenyl-1,3-dioxolan-4-yl)methyl] amino} ethyl)N?,N?-dihydroxyethanediimidamide and its complexes - Canpolat, E; Kaya, M; Öztürk, ÖF (Polish Chemical Soc, 2004)
N,N-Bis(2-{[(2-methyl-2-phenyl-1,3-dioxolan-4-yl)methyl]amino)ethyl)N',N'-dihydr oxyethanediimidamide (LH2) has been synthesized and its mononuclear complexes with Co2+, Ni2+, Cu2+, Zn2+ and Cd2+ ions have been obtained. The mononuclear complexes indicated that the metal ions are ligand coordinated through the two N atoms, as do most of the vic-dioximes. The authenticity of the ligands and their complexes have been established by IR, H-1- and C-13-NMR spectra, UV-Visible spectroscopy, elemental analyses and magnetic susceptibility measurements.
Keywords: dioximes; complexes; transition metals; synthesis of vic-dioxime complexes